2017
DOI: 10.1002/jcp.26167
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in acrolein promoted hepatic ischemia reperfusion injury: Therapeutic potential of NOX2 and p38MAPK inhibitors

Abstract: Neutrophil is a significant contributor to ischemia reperfusion (IR) induced liver tissue damage. However, the exact role of neutrophils in IR induced innate immune activation and liver damage is not quite clear. Our study sheds light on the role of chronic oxidative stress end products in worsening the IR inflammatory process by neutrophil recruitment and activation following liver surgery. We employed specific inhibitors for molecular targets-NOX2 (NADPH oxidase 2) and P38 MAPK (Mitogen activated protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…NETs are the result of a specific type of cell death called NETosis (15) and consist of chromatin filaments and specific granule proteins, including neutrophil elastase (NE) and myeloperoxidase (MPO) (16), which have been associated with the bronchial inflammation and structural damage observed in diseases, such as cystic fibrosis and COPD (17,18). Although NET formation is an antibacterial immune response, it has also been shown to be triggered by constituents of smoke and e-cigarette vapors, such as acrolein (19). E-cigarettes are fairly new products, and data on the effects of their long-term use remain scarce.…”
Section: What This Study Adds To Thementioning
confidence: 99%
“…NETs are the result of a specific type of cell death called NETosis (15) and consist of chromatin filaments and specific granule proteins, including neutrophil elastase (NE) and myeloperoxidase (MPO) (16), which have been associated with the bronchial inflammation and structural damage observed in diseases, such as cystic fibrosis and COPD (17,18). Although NET formation is an antibacterial immune response, it has also been shown to be triggered by constituents of smoke and e-cigarette vapors, such as acrolein (19). E-cigarettes are fairly new products, and data on the effects of their long-term use remain scarce.…”
Section: What This Study Adds To Thementioning
confidence: 99%
“…It has been implicated that CTX, in the presence of cytochrome P450, is metabolized into two unstable and transient intermediates namely, 4ā€hydroxycyclophosphamide and aldophosphamide which are both, in turn, converted into two stable toxic compounds, namely acrolein (propenal, C 3 H 4 O) and phosphoramide mustard (H 6 N 3 OP) (Figure A) . Between these two chemical agents, acrolein, as a highly electrophilic and Ī±, Ī²ā€unsaturated aldehyde, has greater toxicity as it generates higher levels of ROS …”
Section: Introductionmentioning
confidence: 99%
“…Since oxidative stress is considered as one of the main mediator that induces the NETs [36,37], we have assayed the intracellular oxidative stress neutrophils of different experimental animals. Quite interestingly we found that oxidative stress is increased (P < 0.001) in neutrophils isolated from RA rats than that of normal (Fig.…”
Section: Resultsmentioning
confidence: 99%